Integrity of emotional and motivational states during the prodromal, first-episode, and chronic phases of schizophrenia - Yee, Cindy M. (2010)
Emotional and motivational dysfunction is fundamental to schizophrenia, and yet the nature and scope of associated deficits are not well understood. This study assessed the integrity of emotional responding from the perspective of its underlying motivational systems during different phases of schizophrenia. Evaluative, somatic, and autonomic responses were measured during viewing of pictures categorized by emotional content, including threat, mutilation, contamination, illness, pollution, mild erotica, families, food and nature. Participants were 13 patients at ultra high-risk or prodromal for psychosis, 40 first-episode schizophrenia patients, 37 chronic schizophrenia patients, and 74 healthy comparison subjects. Irrespective of phase of illness, schizophrenia patients showed a robust and normal pattern of response across multiple systems, with differential engagement of the defensive and appetitive systems as a function of the motivational significance assigned to specific emotional contexts. Although the integrity of core motivational states also appeared to be intact in prodromal patients, a less consistent pattern of response was observed. As continuing efforts are made to identify emotional and motivational abnormalities in schizophrenia, identified deficits will likely be independent of a fundamental dysfunction in basic emotion and motivation response systems and involve integration with higher order processes.